A New Way of Investigating the Relationship Between Fasting Blood Sugar Level and Drinking Glucose Solution - Aslam, Muhammad; Albassam, Mohammed (Frontiers in Nutrition, 2022)
The existing t-test of a correlation coefficient works under a determinate environment. In uncertainty, the existing t-test of a correlation coefficient is unable to investigate the significance of correlation. The paper presents the modification of the existing t-test of a correlation coefficient using neutrosophic statistics. The test statistic is designed to investigate the significance of correlation when imprecise observations or uncertainty in the level of significance is presented. The test is applied to the data obtained from the diabetic’s patients. From the data analysis, the proposed t-test of a correlation coefficient is found to be effective than the existing tests.